123I Accumulation in Thoracic Neoesophagus Masking Residual Papillary Thyroid Cancer. (February 2015) - Jackson, Tatianie; Sabbah, Nathanael; Iagaru, Andrei
Abstract : Abstract: A 56-year-old woman with prior esophageal resection and reconstruction after accidental lye ingestion presented for management of recently diagnosed thyroid cancer. She had total thyroidectomy with pathology demonstrating bilateral well-differentiated papillary thyroid cancer measuring up to 1.0 cm and positive margins. Approximately 1 month after surgery, 123 I whole-body scan was obtained. Planar images demonstrated linear 123 I uptake in the thorax, compatible with accumulation in the neoesophagus. Given the patient's postsurgical anatomy, SPECT/CT of the thorax was done and demonstrated additional focal 123 I uptake in the left lower neck, compatible with residual thyroid tissue versus thyroid cancer (lymph node metastasis).